2016
DOI: 10.1111/jvim.14610
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Findings in Ascitic Fluid: A Cross‐Sectional Study in 70 Dogs

Abstract: BackgroundAscitic fluids of horses and humans have fibrinolytic activity, independent of the underlying mechanism of fluid formation.ObjectiveTo determine whether coagulation and fibrinogenolytic/fibrinolytic activity (ie, low fibrinogen and increased fibrin–fibrinogen degradation products [FDPs], D‐dimer, or both) occur in all types of ascitic fluid in dogs.AnimalsA total of 70 client‐owned dogs with ascites.MethodsIn this cross‐sectional study, dogs were categorized based on the pathophysiology of fluid form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…Therefore, pleural effusions have inherent fibrin/fibrinogenolytic activity, as has been shown in the case for human [ 26 , 41 , 42 ], and ascitic equine fluid [ 43 ]. In addition, in a recent study on dogs with ascites formed secondary to different pathophysiological mechanisms, we found that also canine abdominal effusions have the same inherent fibrin/fibrinogenolytic activity [ 44 ]. The hypothesis that pleural fluid is inherently fibrinolytic is also supported not only by the clinical observation that pleural effusions rarely form clots in vivo , but also by several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pleural effusions have inherent fibrin/fibrinogenolytic activity, as has been shown in the case for human [ 26 , 41 , 42 ], and ascitic equine fluid [ 43 ]. In addition, in a recent study on dogs with ascites formed secondary to different pathophysiological mechanisms, we found that also canine abdominal effusions have the same inherent fibrin/fibrinogenolytic activity [ 44 ]. The hypothesis that pleural fluid is inherently fibrinolytic is also supported not only by the clinical observation that pleural effusions rarely form clots in vivo , but also by several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have investigated whether coagulation and fibrinogenolytic/fibrinolytic activity occurred in intracavitary effusion by measuring the plasma and the effusion fibrinogen, and the FDPs and D-dimer concentrations of 70 dogs with ascites and 33 dogs with pleural effusion of different pathophysiological origins [ 41 , 72 ]. Abdominal and pleural effusion fibrinogen concentrations in these 103 dogs were undetectable in most cases and significantly lower than those in the plasma while the concentrations of FDPs and D-dimers in the abdominal and pleural fluids were significantly greater than those in the plasma [ 41 , 72 ].…”
Section: Fibrinolytic Activity Of the Intracavitary Fluid In Dogsmentioning
confidence: 99%
“…Abdominal and pleural fluids inherently have fibrinolytic activity [ 41 , 70 , 72 , 75 ] and are in continuous exchange with the systemic circulation [ 75 , 79 ]. Two studies regarding dogs with abdominal and pleural effusion of different pathophysiological origins evaluated whether clotting abnormalities, suggestive of PF/PHF, were more frequent in these dogs.…”
Section: Systemic Fibrinolysis In Dogs With Intracavitary Effusionmentioning
confidence: 99%
See 1 more Smart Citation
“…A ccumulating unnecessary fluid in the peritoneal cavity is a collective pathological condition seen in canines due to various etiologies (Moore et al, 2003, Zoia et al, 2017a. Ascites represent a general systemic state that could manifest in diverse disease conditions in animals.…”
Section: Introductionmentioning
confidence: 99%